Attribute-based access to scalable media in cloud-assisted content sharing - WU, Yongdong (Institutional Knowledge at Singapore Management University, 2013)
This paper presents a novel Multi-message Ciphertext Policy Attribute-Based Encryption (MCP-ABE) technique, and employs the MCP-ABE to design an access control scheme for sharing scalable media based on data consumers’ attributes (e.g., age, nationality, gender) rather than an explicit list of the consumers’ names. The scheme is efficient and flexible because MCP-ABE allows a content provider to specify an access policy and encrypt multiple messages within one ciphertext such that only the users whose attributes satisfy the access policy can decrypt the ciphertext. Moreover, the paper shows how to support resource-limited mobile devices by offloading computational intensive perations to cloud servers while without compromising data privacy.